Natural enemies of Anthonomus eugenii (Coleoptera: Curculionidae) in Canada. Issue 3 (2nd March 2018) - Labbé, R.M.; Hilker, R.; Gagnier, D.; McCreary, C.; Gibson, G.A.P.; Fernández-Triana, J.; Mason, P.G.; Gariepy, T.D.
Abstract: The pepper weevil, Anthonomus eugenii Cano (Coleoptera: Curculionidae), is the most important pest of pepper ( Capsicum Linnaeus; Solanaceae) crops in North America. Native to Mexico, the southern United States of America, and Central America, it is intercepted in Canada when peppers are imported to supplement domestic production. Given the proximity of greenhouse and field production to packing facilities, this pest poses a serious risk to the cultivation of peppers in Canada. Once established, it is difficult to control because immature stages of the weevil are protected within the pepper fruit. As such, chemical control targeting these life stages is not effective, and other strategies, including biological control, may prove useful. To explore the potential for biological control options to manage the pepper weevil in areas at risk in Canada, natural enemy surveys were conducted in southern Ontario following the reports of transient, localised field populations in 2016. Parasitoids belonging to three Hymenoptera families including Pteromalidae ( Jaliscoa hunteri Crawford, Pteromalus anthonomi Ashmead), Eupelmidae ( Eupelmus pulchriceps Cameron), and Braconidae ( Nealiolus Mason species, Bracon Fabricius species) were reared from infested field-collected pepper fruits. Together, these new natural enemy records could facilitate the exploration and development of novel agents for the biological control of the pepper weevil.